Inappropriate shock and battery switching to 'End of Life' in a patient with biventricular ICD during magnetic resonance imaging - İlyas Atar; Uğur Bal; Çağatay Ertan; Bülent Özin; Haldun Müderrisoğlu (KARE Publishing, 2016)
Presence of a cardiac pacemaker or implantable cardioverter defibrillator (ICD) is a relative contraindication to magnetic resonance imaging (MRI). Biventricular ICDs are often used in the treatment of advanced heart failure; however, reports on experience with biventricular ICDs are lacking in the literature. In this case report, we describe a pacemaker-dependent patient with a biventricular ICD on whom an MRI of the lumbar spine was performed without having realized the presence of the ICD.